ANALYSIS OF POSTULATING COMPENSATION ON ENHANCING THE SERVICE QUALITY FOR BARISTA AT COFFEE SHOPS - Dita Oki Berliyanti; Sri Vandayuli Riorini (Journal of Management, Business and Social Sciences, 2023)
The aim of this study was to determine and analyze compensation in improving the quality of service provided by baristas in coffee shop development (case study at 20 Kopi Tirtayasa branch and Langkapura Bandar Lampung branch). This research is descriptive qualitative research using a case study research design. Data collection techniques are by means of interviews, observation, and documentation. The results showed that the compensations given by 20 Kopi to baristas are direct compensation and indirect compensation. Direct compensation in this coffee shop is in the form of salaries and incentives. While indirect compensation is in the form of health insurance. There is a problem with this compensation, which is the low compensation or salary received by baristas at the 20 Kopi Tirtayasa and Langkapura branches. Minimal or inadequate compensation will trigger ineffective employee performance and will have an impact on the quality of service provided to customers. However, despite their low salary, the baristas still give their loyalty to 20 Kopi and provide good quality service to their customers. This will certainly support the development of the coffee shop itself, as 20 Kopi has opened 4 branches in Bandar Lampung. This shows that 20 Kopi has a role as part of the development of coffee shops in Bandar Lampung.